Membranas de quitosana/bioativos naturais com atividade antimicrobiana para tratamento de lesões cutâneas - Santos, Elaine Pereira dos (2018)
Natural antimicrobials are effective and economical alternatives as they are obtained from aromatic plants and rich spices as essential oils characterized by a remarkable antimicrobial activity, and for this reason their products can be used to retard or inhibit the microbial multiplication so found in skin infections. In order to provide quick-relief treatments for wound infection, natural bioactives such as clove and melaleuca oils as well as cashew and noni sprayed juices and powders have been proposed in this work as a research object to obtain an antimicrobial dressing based on chitosan, aiming to optimize the rehabilitation of these lesions. Chitosan membranes containing natural bioactives were prepared by the method of solvent evaporation (casting) and evaluated qualitatively by visual aspect and characterized by thickness, contact angle wettability, swelling degree, Fourier transform infrared spectroscopy (FTIR) , scanning electron microscopy (SEM) and traction test, while chitosan / bioactive emulsions were submitted to antimicrobial activity by the agar diffusion method. Visible light transparency (colorless) presented by pure chitosan membrane underwent changes with the type and concentration of the incorporated bioactive. The chitosan membranes presented contact angle ranging from 40° to 90° in distilled water and PBS, which classified them as hydrophilic materials. Natural bioactives have provided increased membrane hydrophilicity, which is an important result, since wettability is essential in curative materials. The natural bioactives provided improvements in the rate of absorption and stability of the CS1 membrane, especially the clove and melaleuca essential oils that showed significant swelling degrees in distilled water and PBS (rates ranging from 325.23% to 5176.63%). The tenuous properties of pure and incorporated chitosan membranes proved to be sufficient and compatible to be applied as curatives. Clove oil showed the highest inhibition against the microorganisms employed, with halos up to 36 mm (Staphylococcus aureus), followed by melaleuca oil (up to 12 mm Candida albicans) and noni pulp (up to 8 mm Staphylococcus aureus). The incorporation of the natural bioactives provided an increase in the antimicrobial activity of the CS1 emulsion against Staphylococcus aureus (CS1C3), Escherichia coli (CS1C3, CS1M1, CS1M3, CS1CJ3, CS1PCJ3, CS1PN1 and CS1PN1) and Candida albicans (CS1C1 and CS1M3) for such compositions in wound healing. And although the greater inhibition halo (10 mm) was found for the composition with 3% cashew juice compared to Escherichia coli, the essential oils had the highest action spectra. In order to do so, it was concluded that the essential oils of clove and melaleuca were the ones that demonstrated the best antimicrobial activities in the chitosan-based emulsions, presenting as potentially favorable oils in the process healing of skin lesions.